Model of development of methodical competency of a teacher of technologies in the system of postgraduate education - Ostapenko, A. (Problems of Engineer-Pedagogical Education, 2019)
The public policy on education in Ukraine is aimed to reform the system of education in accordance with the principles of humanism, human-centeredness, person-oriented and competence approaches; to imply the best world experience; to democratize the system of education and to ensure the academic freedom of the teacher. The article characterizes the model of the development of methodological competence of a craft teacher in the system of postgraduate pedagogical education, which is based on modern achievements in pedagogical research. It describes the objectives of teacher training at different stages of the development of methodological competence and while doing an advanced training course, such as diagnostic, motivational, activity-technological, reflexive, taking into account the peculiarities of every component of the teacher’s methodological competence and modern principles constructing the educational process in the institution of postgraduate pedagogical education. The article contains an analysis of the scientific sources that shows the existence of the significant number of works dedicated to the implementation of the competence approach in the professional teacher training. At the same time, the issue of a craft teacher’s methodological competence development at different stages of their professional activity and at the stage of taking an advanced training course has not been researched sufficiently. To improve the quality of the educational process in secondary educational institutions of the Kharkiv region, with special emphasis being places on improving the quality of teaching the subject “Crafts”, the author has formulated and tested a model of the development of methodological competence of a craft teacher in the system of postgraduate pedagogical education.